Australian Particle Therapy Clinical Quality Registry (ASPIRE) protocol (TROG 21.12): a multicentre prospective study on patients with rare tumours, treated with radiation therapy - Hien Le; Scott Penfold; Sophie Jessop; Kelly Skelton; Peter Gorayski; Amber Murray; Daniel Hamilton; Adam Yeo; Eunji Hwang; Joshua Dass (BMJ Open)
Introduction In 2020, the Australian Medical Services Advisory Committee (MSAC) recommended new proton beam therapy (PBT) item numbers be added to the Medicare Benefits Schedule. During the MSAC 1638 application process, MSAC recognised the uncertainties inherent in the cost-utility modelling of PBT. To address these uncertainties, MSAC proposed the establishment of a national registry with the intention to gather evidence to validate the claim of PBT’s superior toxicity outcomes and cost-effectiveness compared with conventional photon radiation therapy.Methods and analysis The Australian Particle Therapy Clinical Quality Registry is a prospective, observational, longitudinal registry collecting national data on paediatric, adolescent young adult and adult patients with rare tumours receiving any form of radiation therapy for a defined group of diseases, specified by the MSAC 1638 Public Summary Document. Eligible patients undergoing radiation therapy at participating institutions will be provided with information about the registry, including the opt-out procedure. The registry has no enrolment cap and will persist either indefinitely or until the conclusion of the study.The study design was informed by the Australian Metadata Online Repository and contains a core set of minimum data elements. Representing baseline participant demographics, assessment, diagnosis and treatment; incorporating radiation and systemic therapies, with a specific focus on long-term follow-up, treatment toxicities and specific organ-at-risk testing.Ethics and dissemination There will be no identifying data used in any reports or presentations of data. Additionally, all identifiable data will be safeguarded according to standard practices and available only to the host institution submitting the data to the registry. Aggregated data for the purposes of research will be stripped of identifiers. The registry has been approved under the National Mutual Agreement by the Central Adelaide Local Health Network Human Research Ethics Committee—HREC: 2021/HRE00394.Trial registration number Australian and New Zealand Clinical Trials Registry (ANZCTR): ACTRN12622000026729p.